2017
DOI: 10.1177/2054358117698666
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Rate of Living Donor Kidney Transplantation in Ontario: Donor- and Recipient-Identified Barriers and Solutions

Abstract: Purpose of Review:To hear from living kidney donors and recipients about what they perceive are the barriers to living donor kidney transplantation, and how patients can develop and lead innovative solutions to increase the rate and enhance the experiences of living donor kidney transplantation in Ontario.Sources of Information:A one-day patient-led workshop on March 10th, 2016 in Toronto, Ontario.Methods:Participants who were previously engaged in priority-setting exercises were invited to the meeting by pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 22 publications
2
59
0
1
Order By: Relevance
“…The objectives of this study directly address a priority of living kidney donors and their recipients. 9 Patients were not involved in the design or conduct of this study; however, the results of this study will be disseminated through existing and ongoing patient partnerships. Furthermore, our research group works closely with local organ procurement organizations and patient advocacy groups, such as the Kidney Foundation of Canada.…”
Section: Patient Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives of this study directly address a priority of living kidney donors and their recipients. 9 Patients were not involved in the design or conduct of this study; however, the results of this study will be disseminated through existing and ongoing patient partnerships. Furthermore, our research group works closely with local organ procurement organizations and patient advocacy groups, such as the Kidney Foundation of Canada.…”
Section: Patient Involvementmentioning
confidence: 99%
“…729 Given the outlay of money for travel, parking, and time off work (when applicable), financial costs may pose a barrier for potential willing donors and could be a contributing factor to stagnating rates of living kidney donation. 9 Prior efforts to quantify the costs incurred by living kidney donors have been limited by small sample sizes, retrospective data collection, and incomplete cost data. 8 Furthermore, some groups of donors may incur higher costs; for example, paired kidney donors may incur higher costs for travel, whereas spousal donors may incur higher costs for childcare (or other dependent care) when both parents are receiving medical attention.…”
mentioning
confidence: 99%
“…Mary's case description illustrates how complex it can be for her to receive a living donor kidney transplant, particularly one that is preemptive and avoids exposing her to dialysis. In the province of Ontario in Canada, health professionals, researchers, living donors, recipients, and patients with kidney failure are working together to better understand the barriers that prevent living donor kidney transplants, and to advance solutions which overcome them (26). The literature was reviewed, and expert colleagues were consulted.…”
Section: Solutions To Improve Patient Experiences and Safely Increasementioning
confidence: 99%
“…Connecting patients with peer mentors may help more patients receive a kidney transplant; peer mentors are uniquely able to provide practical guidance and emotional support on the basis of their lived experience. Peer mentorship was highly ranked by recipients and donors at a workshop hosted in Ontario (26), and two clinical trials have shown that more patients receive transplant referrals and progress through the evaluation process when they interact with kidney transplant recipients trained as peer mentors (29,30). In one of these trials (conducted in 134 dialysis centers in Georgia) only about 11% of patients were referred for transplant evaluation in the year after dialysis initiation; this increased to 17% after the intervention (30).…”
Section: Solutions To Improve Patient Experiences and Safely Increasementioning
confidence: 99%
“…4 , 5 However, most ESKD patients never discuss prognosis with their physicians 6 and many patients report that a main barrier to kidney transplantation is limited education. 7 Offering personalized and evidence-based prognostic information has the potential to help patients understand their treatment options and make more informed decisions about their health. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%